Farmer regeneration crisis in villages: Case study of youth in Sragen, Indonesia - Nugroho, Cahyo Bagus Tri; Sugihardjo; Permatasari, Putri; Anantanyu, Sapja (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The rice fields in Sumberlawang District are 1,902 hectares, which are dominated by food crops, therefore the community's main livelihood is as farmers. Farming work has received a poor response from some village youths, young people tend to choose jobs in urban areas by means of urbanization in the hope of earning a high income. The aim of this research is to determine the factors and perceptions of young people in Sumberlawang District following in the footsteps of their parents to become farmers or work in the non-agricultural sector, by analyzing the internal and external factors that influence this. Methods: The method used to obtain and analyze data is a quantitative method supported by qualitative data. Findings: The results of the research show that factors that have a significant relationship with youth regarding farmer work are access to information. Conclusion: Factors that are significantly related to young people's perceptions of farmer work are: formal education and personal experience, while those that are not significantly related are non-formal education, cosmopolitan, and socio-cultural. Novelty/Originality of this Study: Its focus is on understanding the perceptions of rural youth in Sumberlawang District towards agricultural work, with a detailed analysis of the internal and external factors influencing these perceptions. This research provides a comprehensive examination of the significant relationships between formal education, personal experience, and access to information, and how these factors shape youth attitudes towards farming. The study aims to address the declining interest among youth in agricultural professions.